The Effect Of Picture Memory Training On Children's Language Skills - Siswanto, Arif; Pratomo, Hafidz Triantoro Aji (Jurnal Keterapian Fisik, 2024)
Background: Information on how students' academic performance is also determined by their language profile is limited. The use of picture memory exercises has never been provided by teachers in schools. This study aims to determine the effect of picture memory training on improving children's language skills. Methods: This study used an experimental design by giving treatment to children over a period of time and then measuring their language proficiency profile. The intervention was conducted using the picture-memory approach. The study design involved a single-group intervention with assessments conducted before and after the intervention. The target of the intervention is children with language impairment. Results: From the results of the Wilcoxon test, it was found that receptive language skills, especially receptive vocabulary, showed a p-value of 0.002. These results indicate that the picture memory intervention is able to improve receptive vocabulary skills. For expressive vocabulary, a p-value of 0.034 was found. The result also showed that the picture memory intervention was able to improve expressive vocabulary. Picture memory intervention resulted in changes in receptive vocabulary with an r-value of 0.44. Picture memory intervention resulted in changes in expressive vocabulary with an r-value of 0.29. Conclusion: The results of the analysis showed a difference in impact where the receptive vocabulary component was the component that changed more than the expressive vocabulary. However, the provision of a picture memory training intervention can be said to be able to improve language skills in general.